A expectativa da norma programática - Moraes, Ariane Cintra Lemos de (2009)
This work has its objective to analyze the programmatic norms nature and compare them with all other norms of law. This analysis will be made by a sociological observation of Niklas Luhmann s system theory and was chosen and justified because the failure of the traditional understanding of programmatic norms has failed, bringing more damage than good to law, causing more complexity and contingency, irritation and frustration to law and society comparing to others norms. Concepts as norms, constitutional norms, and juridical principles will be analyzed by Luhmannian terms as observation, difference, form, complexity, contingency, irritation and frustration. The core idea of this work is to answer to this question: comparing to other norms what is the difference between the programmatic norms and the others and what does it do to law. The answer of this question on a synthetic way is that those norms don not program anything because it s a communication as any other norms, but its difference rely upon the Constitution as peculiar program as structural coupling that units two autopoietic systems the law and politics